The Relationship between Sleep Disturbances and Glycemic Control in Children with Type 1 Diabetes - Sarfaraz, Sana; Tahir, Bakhtawar; Humaira, Tahir; Faeza, Hasnain (Biological and Clinical Sciences Research Journal, 2025)
Children with Type 1 Diabetes Mellitus (T1DM) require careful glycemic management to prevent both acute and long-term complications. Objectives: To evaluate the association between sleep disturbances and glycemic control in children and adolescents with T1DM and to determine whether sleep quality independently predicts HbA1c levels. Methods: This cross-sectional study was conducted at the University of Lahore Teaching Hospital from September 2024 to February 2025. A total of 185 children and adolescents, aged 6 to 18 years, diagnosed with T1DM for at least 12 months, were recruited for the study. Demographic information, such as age, gender, and diabetes duration, was recorded. Medical data on insulin regimen (MDI or pump), CGM use, and physical activity levels were gathered through parent review of medical records. Results: Sleep disturbances were highly prevalent, with 72% of participants scoring above the clinical threshold on the CSHQ. A moderate positive correlation was observed between sleep disturbance scores and HbA1c (r = 0.41, p < 0.001). Regression analysis confirmed that sleep disturbance score was an independent predictor of HbA1c (β = 0.38, p < 0.001), even after adjusting for confounders. Additionally, children with shorter sleep durations (<7 hours) had significantly higher HbA1c levels (mean: 9.1%) compared to those with ≥9 hours of sleep (mean: 7.7%). Conclusion: It is concluded that sleep disturbances are common in children with T1DM and are significantly associated with poorer glycemic control. Sleep quality should be routinely evaluated as part of comprehensive diabetes management. Targeted interventions to improve sleep may offer a low-cost, behavioral strategy to support better metabolic outcomes in this population.